A shell is cozy - Aston, Dianna Hutts; Long, Sylvia (San Francisco, California : Chronicle Books LLC, 2023)
"From the acclaimed duo Dianna Hutts Aston and Sylvia Long comes this gorgeous look at the fascinating world of shells. From land snails to freshwater mussels, giant clams to tiny, an incredible array of shells are showcased in all their splendor. Poetic in voice and elegant in design, this carefully researched book will spark the imaginations of children in classroom reading circles as well as on parents' laps"--
Includes bibliographical references.
Keywords: Shells -- Juvenile literature